TO TH FORMAL MODELS AS A TOOL IN POLITICAL RESEARCH - T. A. Shebzukhova; A. A. Vartumyan; I. S. Klimenko (Современная наука и инновации)
The urgency of the problem of formalization of political processes and systems and, as a consequence, the need to create tools that provide evidence-based decision-making in the management of systems whose behavior is determined by poorly formalized factors and uncertainty of conditions requires research aimed at the application of existing models and methods of research operations to the problems of political science. The models of political behavior presented in the article are based on the elements of game theory and the idea of optimization. It is obvious that the use of these tools for modeling social and political processes is a nontrivial task, the solution of which will allow to advance in obtaining complex conclusions from a set of initial assumptions to a much greater extent than natural language. The relevance of the problem is determined by the fact that the current state of mathematical modeling in political science is under development. As a rule, we develop models of systems for certain types of tasks and problems that do not meet the modern challenges that society presents to political science.